Combined hepatocellular-cholangiocarcinoma: a rare biphenotypic primary liver cancer. Issue 2 (February 2022) - Lee, Seung Hyun; Luong, Tu Vinh
Abstract: Combined hepatocellular carcinoma-cholangiocarcinoma (cHCC-CCA) is a fascinating and rare primary liver cancer. This biphenotypic neoplasm is characterized by the unequivocal presence of hepatocellular and cholangiocytic histomorphology. Here, we report a case of cHCC-CCA in a 64-year-old man with risk factors for HCC treated with segmentectomy.